Hospital Resource Optimization and Operational Efficiency Through Business Process Reengineering - I Ketut Dian Lanang Triana; Vip Paramarta; Ni Putu Emy Darma Yanti; Ida Ayu Md. Vera Susiladewi (Rey Media Grafika, 2026)
Background: Hospitals are increasingly challenged to improve operational efficiency while maintaining service quality amid limited resources, rising costs, and growing patient demand. In this context, Business Process Reengineering (BPR) has emerged as a strategic approach for fundamentally redesigning hospital processes to improve resource utilization and organizational performance. Objective: This study aimed to analyze the role of BPR in improving hospital resource optimization and operational efficiency, with emphasis on workforce utilization, facility management, and process performance. Methods: A literature review was conducted using four scientific databases: Scopus, PubMed, ScienceDirect, and Google Scholar. Articles published between 2020 and 2025 in English, full-text, and peer-reviewed were included. From 245 initial records, 10 articles met the inclusion criteria and were analyzed narratively. Results: BPR consistently improved hospital efficiency through reduced waiting time, shorter process cycles, lower pharmacy management costs, improved bed turnover, reduced operating room idle time, and better workforce redistribution. Indonesian studies mainly highlighted administrative workflow improvement, pharmacy systems, and digital registration, while studies from the Middle East and Asia emphasized inter-unit coordination and facility utilization. Management commitment, staff involvement, and digital integration were the most frequently identified success factors. Conclusion: BPR remains an effective strategic intervention for optimizing hospital resources. Its impact is stronger when process redesign is integrated with digital transformation and supported by organizational readiness.